2011
DOI: 10.1042/cs20100529
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac peroxisome-proliferator-activated receptor expression in hypertension co-existing with diabetes

Abstract: Hypertension and DM (diabetes mellitus) are common chronic disorders that often co-exist. DM and PPAR (peroxisome-proliferator-activated receptor)-γ agonists may directly impair heart function. However, the effects of DM and PPAR-γ agonists on hypertensive myocardium are not known. Hence the aim of the present study was to investigate whether DM and a PPAR-γ agonist [RGZ (rosiglitazone)] modulated the effects of hypertension on myocardial expression of PPAR isoforms. Cardiac PPAR isoforms, TNF (tumour necrosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 39 publications
2
30
0
Order By: Relevance
“…PGC‐1α is coactivated with members of the PPAR nuclear receptor transcription factor superfamily to activate gene expression involved in mitochondrial fatty acid oxidation . We found a significant decline in both PPAR‐α and PPAR‐δ proteins in parallel to the results of our previous investigations, probably because of the compensatory response to insulin resistance caused by TNF‐α during inflammation . Similar to our previous studies, our study demonstrated that TNF‐α increases PPAR‐γ expression in cardiomyocytes, which might result in cardiac lipotoxicity through its lipogenic effect.…”
Section: Discussionsupporting
confidence: 89%
“…PGC‐1α is coactivated with members of the PPAR nuclear receptor transcription factor superfamily to activate gene expression involved in mitochondrial fatty acid oxidation . We found a significant decline in both PPAR‐α and PPAR‐δ proteins in parallel to the results of our previous investigations, probably because of the compensatory response to insulin resistance caused by TNF‐α during inflammation . Similar to our previous studies, our study demonstrated that TNF‐α increases PPAR‐γ expression in cardiomyocytes, which might result in cardiac lipotoxicity through its lipogenic effect.…”
Section: Discussionsupporting
confidence: 89%
“…It is possible that adult SHR already have increased basal levels of NADPH oxidase activity and AGEs [86, 87] which could not be modulated by diabetes or apocynin. In fact, 3-month old diabetic SHR presented higher cardiac NADPH oxidase activity than control SHR [88]. Thus, apocynin reduced myocardial oxidative stress in SHR-DM-APO through mechanisms not involving NADPH oxidase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found increases in protein and messenger (m) RNA expressions of PPAR-γ, but decreases in protein and mRNA expressions of PPAR-α and PPAR-δ in hypertensive hearts. Diabetic spontaneously hypertensive rats were associated with greater reductions in cardiac PPAR-α and PPAR-δ, but higher increases in PPAR-γ mRNA and protein levels than were spontaneously hypertensive rats [11]. Diabetic cardiomyopathy is associated with an increase in cardiac PPAR-γ and a decrease in PPAR-α, resulting in altered glucose transportation, increased cardiac lipid accumulation, and progressive diabetic cardiomyopathy [7, 1012].…”
Section: Introductionmentioning
confidence: 99%